Les petites populations d'éléphants du Burkina Faso: statut, distribution et déplacements - Philippe Bouché; Clark Lungren (Pachyderm)
This paper reviews the status of several small populations of elephants, representing a total population of 225-230, occupying ranges and corridor areas in Burkina Faso itself, and border regions between Burkina Faso and Togo, Ghana and Ivory Coast in the south, and Burkina Faso and Mali in the north. A table reviews the estimated number of animals and location of 10 of these small populations. They range form about 100 in the Zahre-Red Volta region in northwest Ghana and border area of Burkina Faso border, to about 60 in the Bontioli, Nabere, Mou, and Comoe Valley region in the vicinity of the Burkina Faso, Ivory Coast border, to about 26 in the Diefoula area further west along this same border plus several populations containing less than 10 animals. Map 1 which outlines the general situation and shows the general range areas and major corridors of movement is augmented by three additional maps which focus on specific regions showing ranges and corridor areas in more detail. Although the numerical importance of these small elephant populations appears low at the continental level it is high on the subregional level. Their effect at the local level, whether is be in terms of crop raiding, tourism or potential human-elephant land use needs to be studied and recent aerial surveys of the WAPOK and PONASI ecosystems illustrate a beginning towards this need. (Belemsobgo 2002: Blanc, et al., 2002: Blake, et al. 2003: Bouche, et al. 2004) The authors note the concept of steppping stones in the linking ranges through corridors. (Lahm. 2003)